2014
DOI: 10.5888/pcd11.140272
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Implementing Policy, Systems, and Environmental Improvements to Address Chronic Diseases in Asian Americans, Native Hawaiians, and Pacific Islanders

Abstract: Emphasis has increased recently on disseminating high-impact, population-wide strategies for the prevention of chronic diseases. However, such strategies are typically not effective at reaching Asian Americans, Native Hawaiians, Pacific Islanders, or other underserved communities. The objectives of this article were to 1) present the methods of the Strategies to Reach and Implement the Vision of Health Equity program in which 15 community-based organizations in the United States and the Pacific region implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The immense burden of chronic noncommunicable diseases, particularly regarding disability related to musculoskeletal and mental health conditions, is well established . Accordingly, governments and nongovernmental health‐related agencies worldwide are developing health policy, service, and workforce responses to address this increasing burden , including responses specifically for musculoskeletal conditions . One approach has been the development of models of care (MOCs) to facilitate the planning and delivery of evidence‐informed health care for consumers .…”
Section: Introductionmentioning
confidence: 99%
“…The immense burden of chronic noncommunicable diseases, particularly regarding disability related to musculoskeletal and mental health conditions, is well established . Accordingly, governments and nongovernmental health‐related agencies worldwide are developing health policy, service, and workforce responses to address this increasing burden , including responses specifically for musculoskeletal conditions . One approach has been the development of models of care (MOCs) to facilitate the planning and delivery of evidence‐informed health care for consumers .…”
Section: Introductionmentioning
confidence: 99%
“…32 CBOs selected strategies focused on increasing access to healthy foods: development of community gardens and farmers' markets, implementation of nutrition policies for congregant meals in faith-based settings; and on increasing opportunities for physical activities: implementation of worksite policies for physical activity breaks, school-based joint-use agreements, and promotion of walking trails. Further discussion of funding eligibility, the CHANGE tool, project deliverables and CBO strategies are discussed in Arista et al 47 This report is focused on the four CBOs (herein referred to as Partners) that implemented culturally-adapted community gardens and farmers' markets to highlight successful strategies to increase access to healthy foods for AANHPIs.…”
Section: Strive Program Descriptionmentioning
confidence: 99%
“…Further our group, the New York University Center for the Study of Asian American Health (NYU CSAAH) has demonstrated that health promoting activities are feasible, acceptable, and sustainable by immigrant-serving CBO leadership and members. [14][15][16][17][18] For these reasons, CBOs are ideally situated to play an essential role in dementia care by providing education, addressing social needs, and creating a supportive environment for diverse adults.…”
Section: Introducing Defining and Refining The Role Of Community Organizationsmentioning
confidence: 99%